Framework for component model selection - Aris, H.; Salim, S.S. (2011)
Advances in component-oriented software development research have led, among others, to the birth of a large number of component models, which has caused difficulties to the software developers in selecting the suitable component models to be used. To overcome the difficulties, a framework for component model selection is proposed in this study. The framework allows software developer to specify the criteria of the component model that they would like to use and recommends the component model(s) that fits most of the criteria. An application of the framework shows that it has the potential to be used by the software developers in determining the suitable component models.